Recent advances on natural depsidones: sources, biosynthesis, structure-activity relationship, and bioactivities - Maan T. Khayat; Kholoud F. Ghazawi; Waad A. Samman; Aisha A. Alhaddad; Gamal A. Mohamed; Sabrin RM Ibrahim (PeerJ, 2023)
Depsidones are a class of polyphenolic polyketides that have been proposed to be biosynthesized from oxidative coupling of esters of two polyketidic benzoic acid derivatives. They are principally encountered in fungi and lichens. In addition to their diversified structural features, they revealed varied bioactivities such as antimicrobial, antimalarial, cytotoxic, anti-inflammatory, anti-Helicobacter pylori, antimycobacterial, antihypertensive, anti-diarrheal, antidiabetic, phytotoxic, anti-HIV, anti-osteoclastogenic, and butyrylcholinesterase, tyrosinase, hyaluronidase, and acetylcholinesterase inhibition. The current work was targeted to provide an overview on the naturally reported depsidones from various sources in the period from 2018 to the end of 2022 including their structures, biosynthesis, sources, and bioactivities, as well as the reported structure-activity relationship and semisynthetic derivatives. A total of 172 metabolites with 87 references were reviewed. The reported findings unambiguously demonstrated that these derivatives could be promising leads for therapeutic agents. However, further in-vivo evaluation of their potential biological properties and mechanistic investigations are needed.